Burnout syndrome: stress and the work of the intensivista nurse (Research, Society and Development, 2020)
Objective: to analyze stressors related to Burnout syndrome in intensive care nurses. Method: This work is an integrative review with a qualitative approach, elaborated from a bibliographic survey, using books and scientific articles.  Virtual research libraries were used for data collection: Scientific Electronic Library Online (SCIELO) and Latin American and Caribbean Literature in Health Sciences (LILACS). Results: it is evident in the literature that the ICU nurse has more proximity to work stress, in addition to having his sleep impaired by excessive workload, which ends up being a relevant factor when we talk about quality of service and worker health, and thus is the most affected by Burnout Syndrome. Conclusion: With regard to Burnout Syndrome, the importance of caring for the worker so that he does not get sick and camouflage with the problems related to mental attrition is evident, since we know how exhaustive the activity of the intensive care nurse is, as well as the correct execution of the behaviors inherent to his work development.